2015
DOI: 10.1093/mutage/gev020
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles: correlating nanoparticle size and cellular uptake with genotoxicity

Abstract: The focus of this research was to develop a better understanding of the pertinent physico-chemical properties of silver nanoparticles (AgNPs) that affect genotoxicity, specifically how cellular uptake influences a genotoxic cell response. The genotoxicity of AgNPs was assessed for three potential mechanisms: mutagenicity, clastogenicity and DNA strand-break-based DNA damage. Mutagenicity (reverse mutation assay) was assessed in five bacterial strains of Salmonella typhimurium and Echerichia coli, including TA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 59 publications
3
113
2
4
Order By: Relevance
“…Interestingly, GNP selectively inhibited the proliferation of myeloma cells, but had no effect on the proliferation of human peripheral blood lymphocytes (PBL) . Similarly, exposure of experimental animals to SNP has been shown to cause anemia, cardiac enlargement, growth retardation and degenerative changes in the liver (Butler et al 2015). With regard to the immune system, the viability of human PBL was decreased in time-and dose-dependent manners upon exposure to SNP in vitro (Ghosh et al 2012;Vergallo et al 2014;Zhornik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GNP selectively inhibited the proliferation of myeloma cells, but had no effect on the proliferation of human peripheral blood lymphocytes (PBL) . Similarly, exposure of experimental animals to SNP has been shown to cause anemia, cardiac enlargement, growth retardation and degenerative changes in the liver (Butler et al 2015). With regard to the immune system, the viability of human PBL was decreased in time-and dose-dependent manners upon exposure to SNP in vitro (Ghosh et al 2012;Vergallo et al 2014;Zhornik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nanoscale materials have achieved considerable attention as novel antimicrobial agents due to their high surface area-to-volume ratio and distinct physical and chemical properties. [5][6][7] The extremely strong broad-spectrum antimicrobial property of AgNPs is the key direction for the improvement of AgNPs-based biomedical products, including bandages, catheters, antiseptic sprayers, textiles, and food storage containers. and pyrolysis; 21 of these, chemical reduction has been the most common route to synthesize nanosilver.…”
Section: Introductionmentioning
confidence: 99%
“…long-term health effects, especially, cancer. Studies that utilized the Ames test measuring point mutations in bacterial stains of S. typhimurium and/or E. coli reported that AgNPs tested negative for mutagenicity in bacteria (Butler et al, 2015; Guo et al, 2016). The lack of mutagenicity was explained by the inability of bacteria to take up AgNPs (Butler et al, 2015; Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that utilized the Ames test measuring point mutations in bacterial stains of S. typhimurium and/or E. coli reported that AgNPs tested negative for mutagenicity in bacteria (Butler et al, 2015; Guo et al, 2016). The lack of mutagenicity was explained by the inability of bacteria to take up AgNPs (Butler et al, 2015; Guo et al, 2016). However, AgNPs induced mutagenic and clastogenic effects in mammalian cells as shown by mouse lymphoma and micronucleus assays, respectively (Butler et al, 2015; Guo et al, 2016; Vecchio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%